2022
DOI: 10.3389/fphar.2022.924473
|View full text |Cite
|
Sign up to set email alerts
|

Role of resveratrol in inhibiting pathological cardiac remodeling

Abstract: Cardiovascular disease is a group of diseases with high mortality in clinic, including hypertension, coronary heart disease, cardiomyopathy, heart valve disease, heart failure, to name a few. In the development of cardiovascular diseases, pathological cardiac remodeling is the most common cardiac pathological change, which often becomes a domino to accelerate the deterioration of the disease. Therefore, inhibiting pathological cardiac remodeling may delay the occurrence and development of cardiovascular diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 213 publications
1
9
0
Order By: Relevance
“…Alcohol consumption had a protective role on mortality in our cohort, unlike in the literature ( 43 ), probably due to wine consumption rather than spirits. Red wine is a source of polyphenols, such as resveratrol and anthocyanin, with demonstrated antioxidant properties and protective role against cardiovascular diseases ( 44 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption had a protective role on mortality in our cohort, unlike in the literature ( 43 ), probably due to wine consumption rather than spirits. Red wine is a source of polyphenols, such as resveratrol and anthocyanin, with demonstrated antioxidant properties and protective role against cardiovascular diseases ( 44 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of natural medicinal herbs in the treatment of cardiovascular disease is gradually gaining acceptance, and have been used in the clinical management of DCM for many years. Studies have also confirmed that some herbal formulas (Sun et al, 2017;Peng et al, 2022) and natural compounds can inhibit apoptosis (Fan et al, 2022), improve mitochondrial energy metabolism (Duan et al, 2015) and inhibit myocardial fibrosis (Chen Q. et al, 2022). A study of herbs associated with cuproptosis showed that most natural compounds, such as resveratrol and quercetin, mainly depend on folic acid to regulate cuproptosis-related genes (CRGs) (Dayuan et al, 2023).…”
Section: Introductionmentioning
confidence: 95%
“… 396 Stimulation of SIRT3 reduces ROS and protein kinase levels and prevents cardiac hypertrophy, which may be a mechanism to inhibit cardiac remodeling. 397 Last, p300 is a potential therapeutic target for heart failure. Mice with p300 knockout exhibit remarkable cardiac defects and embryonic lethality (Table 3 ).…”
Section: Acetylationmentioning
confidence: 99%
“…The sirtuin family also plays key roles in preventing cardiomyocyte fibrosis, regulating cardiomyocyte apoptosis, improving cellular energy metabolism remodeling and inflammation, and maintaining cardiac homeostasis 396 . Stimulation of SIRT3 reduces ROS and protein kinase levels and prevents cardiac hypertrophy, which may be a mechanism to inhibit cardiac remodeling 397 . Last, p300 is a potential therapeutic target for heart failure.…”
Section: Acetylationmentioning
confidence: 99%